Latihan Passing Terhadap Akurasi Efektivitas Modifikasi Latihan Passing Terhadap Akurasi Short Passing Pemain Sepakbola SSB Kuda Kuningan - Sukma Pratama, Panji; Fauzan, Elang (Journal of Physical Education and Sport Science, 2025)
Panji Sukma Pratama (NIM 182223088), Effectiveness of Modification of Passing Exercises on Short Passing Accuracy of SSB Kuda Kuningan Soccer Players, Physical Education Health and Recreation (PJKR) in 2022. The purpose of this study was to obtain information about the effect of modifying cube-shaped passing exercises on passing accuracy of SSB Kuda Kuningan Soccer Players. The research method used is the experimental method. The population in this study were SSB Kuda Kuningan football players with a sample of 20 people. The research instrument used by researchers for passing accuracy is the passing test. Based on the results of research, data processing, data analysis, and hypothesis testing, it was found that there was a significant influence in the modification of cube-shaped passing exercises on the passing accuracy of SSB Kuda Kuningan football players. Based on the data analysis of the increase in experimental class results, the first hypothesis that the author proposes is that t count (3.284) is greater than t table (2.878), so (Ho) is rejected and (Ha) is accepted. This means that passing exercises with variations in the shape of the cube can be said to have an effect on the passing accuracy of SSB Kuda Kuningan players. Based on the data analysis of the improvement in control class results, the second hypothesis that the author proposes is that t count (-557) is smaller than t table (0.688), so (Ho) is accepted and (Ha) is rejected. It means that ordinary practice without being modified into a cube-shaped passing exercise has no effect on the passing accuracy of SSB Kuda Kuningan players.